A comprehensive analysis on the state‐of‐the‐art developments in reflectarray, transmitarray, and transmit‐reflectarray antennas. Issue 9 (16th May 2020) - Narayanasamy, Kavitha; Mohammed, Gulam Nabi Alsath; Savarimuthu, Kirubaveni; Sivasamy, Ramprabhu; Kanagasabai, Malathi
Abstract: Contemplating the advancements in communication technology, the analysis of the features of reflectarray, transmitarray, and transmit‐reflectarray becomes essential for future adaptability. This article presents a thorough review of such high‐gain antennas, presenting some of the most relevant solutions published by the scientific society in the field of antennas and wave propagation. Several examples of unit cells for array implementation and complete array designs discussed in various literatures are analyzed. The analysis is focused in identifying the unit cell layouts, such as those developed using microstrip patches, frequency selective surfaces, or metamaterials. The analysis is extended to the ways of improving bandwidth, for example, true time delay elements, phase delay lines, meander lines, and so on, and the various methods used to enable reconfiguration, for example, p‐i‐n diodes, varactor diodes, or microelectromechanical systems. In addition, some antennas, which produce bidirectional beams simultaneously, are also discussed. Finally, all the models are compared against each other in order to highlight their benefits and limitations, summarizing their main characteristics, such as the frequency of operation, bandwidth, phase range, gain, aperture efficiency, sidelobe levels, cross polarization levels, and maximum beam‐steering range.